Real Timetopias - Rodrigo Delso (lo Squaderno, 2018)
In one nanosecond of the Earth, all seasons, all animals, all lighting conditions, all social activities, all dramas, all sports or all hours happen at once. Trillions of things coexist in different spaces but at the same time and none usually cares.